Management research : applying the principles of business research methods - Rose, Susan; Spinks, Nigel; Canhoto, Ana Isabel (New York, NY : Routledge, 2024)
"Management Research: Applying the Principles of Business Research Methods supports new researchers on every step of the research journey, from defining a project to communicating its findings, as well as balancing the technical aspects of research with the management of the project itself. Structured around the key stages of a research project, the text reflects the richness and diversity of current business and management research, both in its presentation of methods as well as its choice of examples drawn from different industries and organizations. This book explains the design, selection, development and implementation of appropriate research strategies in different management contexts and disciplines, providing practical guidance to the new researcher in carrying out ethical and inclusive research in today's organizational and business environments, whilst also introducing a range of research methods and techniques. Each chapter includes learning outcomes and in-chapter call out boxes with real-life research examples to illustrate concepts and provide basis for discussion, as well as 'next steps' activities to help readers apply the content to their own live research projects. This second edition has been updated throughout to include: enhanced pedagogical features such as discussion questions and online quizzes new international examples and research-in-practice cases greater emphasis on topics such as: Diversity and Inclusion through the research process, data collection and privacy, digitalisation, and the process of writing up research. Management Research provides essential reading for undergraduate and postgraduate students undertaking a dissertation, thesis or research project, as well as professionals currently practicing in the field. Extensive instructor and student resources support the work online, including an instructor's manual, PowerPoint lecture slides, a question bank and downloadable MS Excel and SPSS data sets, as well as video tutorials that support the development of practical research skills"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Management -- Research; Quantitative research